Effects of Back Massage and Facial Massage on Sleep Quality in Critically Ill Patients - Ghazal, Sawsan (Latakia University Journal -Medical Sciences Series, 2014)
Introduction: Sleep disturbance is common among patients in intensive care units (ICUs). Changes in clinical practice to promote sleep in the ICUs have been sporadic. The European Respiratory Society and the European Society of Intensive Care Medicine recognize that massage therapy may improve quality of sleep. Goal: This study was conducted to identify the effects of back and face massage on sleep quality in ICU patients. Material and Methods: A sample of 45 patients in intensive care units in Al-Assad University Hospital and Alwatani Hospital were recruited in the study. Both the massage and control participants were evaluated for sleep quality by Groningen sleep quality scale, 1 hour after administration of the protocol. Results: The effectiveness of back and face massage, as quality of sleep, is significantly improved (p=0.000) in the experimental back and face massage groups (mean score 3.9981), and (mean score 4,4043) respectively, than in control group (mean score – 0.8117). In conclusion, our data suggest that back and face massage therapy is effective in improving the quality of sleep in ICU patients. المقدمة: يعد اضطراب النوم من الاضطرابات الشائعة في وحدات الرعاية المركزة، والتغيرات التي حدثت في الممارسة السريرية الموجهة لدعم النوم في وحدات الرعاية المركزة متفرقة، ميزت جمعية الجهاز التنفسي الأوروبية والجمعية الأوروبية للطب والعناية المركزة أن العلاج بالتدليك قد يحسن نوعية النوم. الهدف: قد أجريت هذه الدراسة لتحديد تأثير تدليك الظهر وتدليك الوجه على نوعية النوم في مرضى الحالات الحرجة. طرائق البحث وأدواته: أجري البحث على عينة قوامها 45 مريضاً في وحدات الرعاية المركزة في مستشفى الأسد الجامعي والمستشفى الوطني. تم تقييم نوعية النوم في المجموعتين التجريبيتين والمجموعة الضابطة باستخدام مقياس نوعية النوم Groningen بعد ساعة من تطبيق السياسة. النتائج: أوضحت النتائج فعالية تدليك الظهر وتدليك الوجه، إذ تحسنت نوعية النوم بشكل ملحوظ (** P = 0.000) في المجموعة التجريبية التي تلقت تدليك الظهر والمجموعة التجريبية التي تلقت تدليك الوجه بقيمة متوسطة (3,9981) و (4,4043)على التتابع، أكثر من المجموعة الضابطة التي لم تتلق التدليك وتركت لروتين المشفى. الاستنتاجات: تقترح معلومات الدراسة أن تدليك الظهر وتدليك الوجه علاجان فعالان في تحسين نوعية النوم في مرضى الحالات الحرجة.